Lirski cikel ali lirska pesnitev? - Žerjal-Pavlin, Vita (Slavistična revija, 2008)
With genre destignation, authors influence the literary reception and at least partially literary analysis. The article examines reasons for the designation "long poem", used for their texts by the contemporary Slovene poets Gregor Strniša and Boris A. Novak. Using the terms "long poem", five-part poem", and "ballad", Strniša after the fact debated with the established characterization of his texts by literary scholars as lyric sequences. Novak termed a long poem Kamnita Afrodita, one of three texts in his book Hči spomina (1981), as well as the book Tisoč in en stih (1982), which prompted the same designation for two more of his texts from the book Hči spomina.
Keywords: literarne vrste; Novak, Boris A., 1953-; Slovene literature; slovenska književnost; slovenska poezija; Strniša, Gregor, 1930-